Pós-colheita de sementes e produção de mudas de Copernicia. - Viana, Erivanda de Oliveira (2019)
The genus Copernicia belong to Arecaceae family, that are distributed in the tropical regions and presents social, economic and landscape importance. The species of this genus have wide utilities, because all plant is utilized, providing different products. In face of her importance, the objective of this research was to evaluate morphometric characteristics of seeds, morphology of germination and initial growth in different conditions of shadings of the species Copernicia alba, Copernicia hospita, Copernicia macroglossa and Copernicia yarey and the effect of storage of seeds in different ambiences and packs of the Copernicia alba. The morphometric analysis were realized by analyzing images obtained from the Groundeye S 800 apparatus and of X-ray images. In the morphology of germination the initial structures were photographed, edited and sequenced in accord with development of plant. In the analysis of initial growth the seeds were sowing in tubes and distributed in four levels of shadings (0, 30, 50 and 70%). In the storage the seeds were putted in three packs (PET bottles, paper bags and raffia bags), storage in natural ambience and cold chamber for five periods (0, 4, 8, 12 and 16 months). After each period tests were realized to determinate the physiological quality. The results of morphometric analysis of the seeds and identification of coleoptera Pachymerys sp. by means of X-ray images analysis were efficient and considered innovative methods to these species. About seedling of Copernicia during the initial growth expressed positives effects when cultivated in full sun and 30% of shading with satisfactory quality indexes. In the effect about the storage of the seeds in the three packs, the percentage of emergency of plants kept above 70%, until 16 months of storage in cold chamber. In face of theses results, the data obtained are important and promising, contain informations that will help in the identification and conservation of these species, in the establishment of seedling production, as well will can corroborate in future researchs.